A regulamentação e a circulação de livros de leitura e gramáticas primárias no Pará oitocentista - SÁ, Arlene da Costa (2022)
This study has as general objective to analyze the regulation and circulation of reading books and primary grammars in the nineteenth century Pará. Therefore, we seek to understand the ideologies that guided the approval of school books for instruction/primary education in schools in the nineteenth century Pará; to investigate the legislation that regulated the teaching of reading and grammar in the nineteenth century Pará and to investigate the circulation of reading books and primary grammars in schools in the nineteenth century Pará. The source of research is the journal Education and Teaching, 33 editions published in the period from 1891 to 1895. The theoretical-methodological orientation of the work is based on the studies of Faria Filho (2000), Duarte (2018), Coelho and Maciel (2018), Karnal and Tatsch (2009), Razzini (2014) and Moreira (1979). The research is part of studies on the constitution of the history of the school book in the Amazon. The results showed that many of the regulations/legal precepts about the instruction/education in Pará were not (and are not) implemented, or were belatedly, sometimes for lack of necessary infrastructure or by the historical inchance of the rulers. From the research in the pedagogical journal Education and Teaching, 22 school compendiums were counted, between reading books and primary grammars, that circulated in the nineteenth century Pará, by authors from Pará and non-Pará. These works were fundamental for the instruction/education of Pará. Political, cultural, religious and even economic aspects were involved in the process of approving these textbooks to circulate in schools in Pará.